Influence of waiting time on the satisfaction of users attended in the facilities of the Ministry of Health and Social Health Insurance - Erika Beatriz García Castro, Andrés Vilca Mamani, Roberto Arpi Mayta, Tomas Tisnado Chura (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of the research is to determine the incidence of waiting time for consultation and appointment scheduling on the satisfaction of users of the facilities of the Ministry of Health (MINSA) and Social Health Insurance (ESSALUD). The research methodology is quantitative of causal type, using the Ordered Logit model, with a sample of 3,644 users of the Ministry of Health and 1,211 users of the Social Health Insurance from the National Household Survey (ENAHO). The probability of satisfaction among MINSA users is 82% with an average waiting time of 41 minutes and 0.7 days to schedule an appointment, while for ESSALUD satisfaction is 75% with 56 minutes of waiting time for a consultation and 6.8 days to obtain a medical appointment. The probability of satisfaction in both facilities decreases for every 10 minutes of waiting time for consultation and for every additional day of waiting time to obtain a medical appointment. Dissatisfaction is even worse after 60 minutes, and it is also observed that patients in the extreme poor and non-extreme poor groups reveal greater satisfaction than those in the non-poor groups. Patients spend more time waiting to be attended in the doctor's office and to obtain a medical appointment than consulting with health professionals.